ANALISIS ESTETIKA ANIMASI 2 DIMENSI CERITA RAKYAT ASAL-USUL BATURRADEN PADA YOUTUBE DONGENG TANAH JAWA - Amirah, Yumna (LPPM Institut Teknologi Telkom Purwokerto, 2023)
Baturraden is one of the areas in the province of Central Java. The name Baturraden was created from folklore. In fact, not many local people, especially children, know the origins of the creation of Baturraden. Therefore we need media that can attract the attention of children namely is through 2-dimensional animation which can be accessed easily via YouTube. This study uses a qualitative descriptive analysis approach using the science of aesthetics. The theory of aesthetics uses a theoretical approach according to Djelantik which describes aesthetics into three basic elements, namely form, weight, and appearance. A 2-dimensional animation of the folk story